Evaluación de la actividad de anticuerpos, interferon y células inmunocompetentes contra parásitos intracelulares - Ferreira V., Arturo; Schofield, Louis (Avances en Ciencias Veterinarias, 1988)
In this review the activity of antibodies, interferon and immunocompetent cells against intracellular parásitos is discussed under the current concepts of basic immunology by means of an experimental malaria model.